2017
DOI: 10.1016/j.knee.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of joint angle and movement velocity on sex differences in the functional hamstring/quadriceps ratio

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…8). Some studies investigated the effect of sex on functional HQ ratio at different angles (i. e., 15º, 30º and 45º), with results showing lower ratio in females independently of knee angle [25], or a reduced ratio in females at more extended knee positions [24]. By using a wider range of motion as well as a continuous SPM analysis, the current study suggests that female skiers have lower HQ ratios than male skiers beyond 38º of knee extension.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…8). Some studies investigated the effect of sex on functional HQ ratio at different angles (i. e., 15º, 30º and 45º), with results showing lower ratio in females independently of knee angle [25], or a reduced ratio in females at more extended knee positions [24]. By using a wider range of motion as well as a continuous SPM analysis, the current study suggests that female skiers have lower HQ ratios than male skiers beyond 38º of knee extension.…”
Section: Discussionmentioning
confidence: 56%
“…Albeit higher peak torque value for both knee extension and knee flexion have been commonly reported in males compared with females, there are conflicting data regarding the impact sex has upon HQ ratio. Some studies reported lower ratio in females than males [25] irrespective of moment velocity and joint angle, whereas others reported a sex-difference specifically at more extended knee positions [24], or at low angular velocity [4] or on the contrary at faster velocities [24,33]. In addition, it has been suggested that sex differences have also an effect on the torque-angle relationship of hamstrings and quadriceps [17,54].…”
Section: Amtmentioning
confidence: 99%
“…Quadriceps and hamstring peak forces, as well as forces at specific joint angles, were multiplied by the length (m) of the isokinetic dynamometer lever arm and normalized by the body mass (kg) of the athlete to obtain the normalized torques ( as peak concentric and eccentric quadriceps torque production is likely to occur in the mid-late range of the movement (40-80 ° of flexion) [17,59].…”
Section: Discussionmentioning
confidence: 99%
“…There was only a significant increase in peak hamstring torque at 30 °•s − 1 (eccentric) between T initial and T final (p = 0.05, ES = − 4.81) that must be considered when interpreting the stability of the functional ratio. According to recent studies by De Ste Croix et al and El-Ashker et al, a joint-angle-specific approach allows at this point a more functional and comprehensive overview [17,59].…”
Section: Effect Of the Fatigue Protocol On Knee Stabilitymentioning
confidence: 99%
“…The aforementioned prospective studies that quantified eccentric knee flexor (eccKF) and concentric knee extensor (conKE) strength at angular velocities of ≤ 120°•s -1 are substantially lower than the knee angular velocities exhibited during tasks associated with injury (~400°•s -1 ) (Nedergaard et al 2014). Thus, adopting higher angular velocities for the assessment of eccKF and conKE strength may also identify strength discrepancies that are increasingly relevant to movements performed in soccer, and may subsequently enhance the functional relevance of outcome measures (De Ste Croix et al 2017).…”
Section: Introductionmentioning
confidence: 99%